The Influence of Website Usability, Social Media Engagement, and Omnichannel Integration on the Digital Customer Experience of Online Retail - Hendratni, Tyahya Whisnu; Hamdany, Mohammad Azharie; Nawangwulan, Irma M; Anantadjaya, Samuel PD; Nurdiansyah, Yanuar; Violin, Vivid (Journal of Current Research In Multidisciplinary, 2026)
The research study investigates the impact of three factors which are Website Usability Social Media Engagement and Omnichannel Integration on Digital Customer Experience in online retail websites. The study used a quantitative approach with a survey method by distributing questionnaires to 200 active online retail consumers selected using a purposive sampling technique. The research required respondents to meet three requirements which included making two online purchases within the previous six months and using social media platforms and accessing multiple digital channels from different companies. The research team used multiple linear regression analysis to process the collected data. The data underwent testing before the analysis process through validity testing and reliability testing and classical assumption testing which included assessments of normal distribution and testing for heteroscedasticity and multicollinearity. The study proved that Website Usability together with Social Media Engagement and Omnichannel Integration created a positive relationship which reached a statistically significant impact on Digital Customer Experience. The results demonstrate that three factors which include website usability and social media customer engagement and cross-channel service integration show a strong impact on digital customer experience in online retail stores.